The Fertile Darwins: Epigenesis, Organicism, and the Problem of Inheritance - Griffiths, Devin (Romanticism and Victorianism on the Net, 2016)
This essay explores the Darwinian imagination – an approach to exploring the basic ontology of nature that was shared by both Erasmus Darwin and his grandson, Charles Darwin. It focuses on Erasmus and Charles’s respective theories of generation, especially as laid out in Zoonomia (1794) and The Variation of Animals and Plants Under Domestication (1868), and their derivation from the longstanding opposition between theories of epigenesis and panspermia. Erasmus Darwin’s thinking, in particular, was torn between relatively closed and open conceptions of how organic structures assemble and reproduce. Charles, by contrast, worked hard to fashion his theory of pangenesis into a capacious model that would account for interactions of inheritance and development across all levels of physical and temporal scale. Yet beneath disagreements over the distribution of agency between matter and different sexual partners, both argued for an anti-holist, anti-organic ontology that consistently cleared space for more open, more contingent, and ultimately more ecological theories of nature. Ultimately this required a rejection both of the Romantic conception of organic life and Romantic aesthetics, in particular, the notion that the unity of aesthetic experience communicated something about the unity of natural systems. Finally, I will argue that Charles Darwin’s pangenic model – which relies upon the functional assemblage of elements derived from different lineages, on different timescales, and with distinct, non-overlapping, and incompletely integrated capacities – offers a unique way of understanding the problem of intellectual inheritance and the relation between the Darwins themselves. If most approaches to this problem have posited either a lineal genealogy of intellectual inheritance, or situated their work as reflections of a larger historical context, pangenesis can help to imagine intellectual history beyond our typically lineal or atmospheric models of influence.